The Influence of Peers and Financial Learning in Higher Education on Financial Literacy - Syahnaz, Helwa Insania; Rustiana, Ade; Srigustini, Astri (Economic Education and Entrepreneurship Journal, 2023)
Financial literacy is important for individuals so that individuals are better at managing their finances. Good financial literacy can prevent individuals from financial problems. This study aims to determine the effect of peers and financial learning in college on financial literacy. This research method uses a quantitative survey method with an explanatory design. The population used was students of the Department of Sharia Economics, Economics Education, Accounting, Management, Finance and Banking, and Agribusiness Class of 2020 at Siliwangi University, totaling 1013 respondents. The sampling technique used is propotional random sampling with the slovin formula. Meanwhile, the data collection technique in this case uses a questionnaire and the data analysis technique uses multiple linear regression tests. The results showed that 1) there is no positive and significant influence between peers on student financial literacy with a significance value of 0.608 2) there is a positive and significant effect of financial learning in college on student financial literacy, which is 0.000.Keywords: Financial Learning in Higher Education, Financial Literacy, PeersDOI: http://dx.doi.org/10.23960/E3J/v6i2.139-144